133k views
5 votes
Solve the inequality:

3z−1≤−7

Select one:

z≥2

z≥−2

z≤−2

z≤2

User UserAbhi
by
4.7k points

2 Answers

4 votes

Answer:


z \leqslant - 2

Step-by-step explanation:

1) Add 1 to both sides.


3z \leqslant - 7 + 1

2) Simplify -7 + 1 to -6.


3z \leqslant - 6

3) Divide both sides by 3.


z \leqslant - (6)/(3)

4) Simplify 6/3 to 2.


z \leqslant - 2

Therefor, the answer is Option C.

User Per Fagrell
by
4.9k points
3 votes
Answer:

z ≤ -2

Step-by-step explanation:

3z − 1 ≤ -7

3z ≤ -6

z ≤ -2
User Radix
by
5.7k points